Comparison of UK paediatric consultants' participation in child health research between 2011 and 2015. Issue 8 (24th February 2017) - Winch, Rachel; McColgan, Martin; Modi, Neena; Greenough, Anne
Abstract : Objective: To identify whether there have been changes over time in the capacity of paediatric consultants to undertake research and if the activity differs between men and women. Design: Comparison of data from two surveys of UK paediatric consultants. Subjects: UK consultant members of the Royal College of Paediatrics and Child Health. Interventions: Surveys carried out in 2011 and 2015. Main outcome measures: The proportion of consultants with allocated time in job plans for research, academic appointments, postgraduate qualifications, publications, grant funding and supervision of PhD students. Results: The 2015 survey demonstrated 20% of consultants had one or more programmed activities (PAs) for research, but the average paid PA for research was 0.39 PA. Between the surveys, the proportion of consultants with honorary contracts had declined, and the proportion with a PhD or MDRes was 32% in 2011 compared with 26% in 2015 (p<0.001). In 2015, only 12% of consultants had at least one current grant. In 2011 and 2015, 51% and 54% respectively of consultants had not authored a publication in the preceding 2 years. In 2015, 92% of consultants were not currently supervising a PhD student, and 88% had never supervised a PhD student. In 2015, 25% of men and 12% of women had PAs for research (p<0.001). Women were less likely to hold an honorary or primary academic contract, have authored a publication or supervised a PhD student (all p<0.001). Conclusions: Research activity among paediatric consultants remains low, particularly among women.